Local Media Editorial Policy in Yogyakarta in News of Covid-19 (Case Study Editorial Policy in Harian Jogja and Tribun Jogja in News Of Covid-19) - Andreas Tri Pamungkas; Olivia Lewi Pramesti (BPSDMP Kominfo Manado, 2021)
Local mass media play a role in disseminating information about Covid-19. The news of Covid-19 is included in the editorial policy of the media because it contains important news value (significance). Editorial policies are important to research because the Covid-19 problem affects all aspects of life in society from politics, economy, social and culture. This study will look at the editorial policies of local media in Yogyakarta, Jogja Daily and Tribun Jogja in reporting on Covid-19. Researchers want to see how local media play an active role as a source of information that educates and improves the welfare of the community through its editorial policies. The editorial policy will be seen through the Gans story selection approach. The method in this research is a case study by conducting in-depth interviews with the editor. The editorial policy is seen from the period March 2021 to April 2021. The results show that the two local media prioritize the Covid-19 prevention agenda. Daily Jogja and Tribun Jogja saw that the local government did not have readiness in mitigating the pandemic, thus making the two local media editors have different sharpening in each aspect of choosing Gans stories, namely (1) source considerations, (2) substantive considerations, (3) product considerations, (4) value considerations, (5) commercial considerations, (6) audience considerations, and (7) political considerations.